La Revolución Mexicana en la prensa revolucionaria de América del Sur, 1910-1914. ¿Una «Comuna» americana? - Garrido González, Pablo (Pontificia Universidad Católica del Perú, 2026)
This study aims to examine how Magonism and the Mexican Revolution were received, spread, and understood among anarchist and revolutionary groups in the southern part of the Americas from 1910 to 1914. The research focuses on the anarchist and syndicalist movements in Argentina, Chile, and Peru. It seeks to identify the networks and interactions that contributed to the dissemination of Magonism in the region. Additionally, it describes the key translations and controversies, both local and international, related to the promotion, analysis, and challenges of the social revolution in Mexico.

Este trabajo busca caracterizar la recepción, difusión y exégesis del magonismo y de la Revolución Mexicana entre los círculos anarquistas y revolucionarios del extremo sur del continente americano entre 1910 y 1914. Mediante el análisis de la literatura disponible y una selección de fuentes primarias representativas del movimiento anarquista y sindicalista en Argentina, Chile y Perú, se busca identificar las redes e intercambios que facilitaron la difusión del magonismo en la región. En segundo lugar, se describen las principales traducciones y polémicas, tanto nacionales como transnacionales, a propósito de la propaganda, análisis y vicisitudes de la revolución social en territorio mexicano.
The Mexican Revolution in the revolutionary press of South America, 1910-1914. An American «Commune»?
Keywords: Mexican Revolution; South American anarchism; Magonism; Revolutionary press; Revolución Mexicana; Anarquismo suramericano; Magonismo; Prensa revolucionaria; https://purl.org/pe-repo/ocde/ford#6.01.01